Plan turístico comunitario en la comunidad Quislag grande, parroquia Tixán, cantón Alausí, provincia de Chimborazo - Pacto Morocho, Juan Eduardo (2023)
The purpose of this study is to "Propose a plan for the tourism development of the Quislag Grande Community, Tixán Parish, Alausí Canton, Province of Chimborazo. The results of the participatory diagnosis (meetings with residents and surveys of leaders) determined that it is a mainly agricultural sector with a high level of migration of young people and tourism is not supported by the authorities while the community is unaware of tourism and its benefits. The SWOT evaluation using the MEFI and MEFE showed that they are favorable because the strengths and opportunities outweigh the weaknesses and threats, generating strategies for using and taking advantage of the available tourist attractions. The projects were proposed based on the strategic axes that emerged from the SWOT analysis, focused on tourism development such as the creation of the tourism unit, establishment of new attractions, tourism signage, community training and tourism marketing. It was concluded that in the Quislag Grande community tourism has not been exploited because it has not been taken advantage of due to the lack of tourism planning; however, this research allowed discovering and capturing all the tourism information that the community has, in which flora and fauna were found, many of which are native to the region and given its climate, originally from the highlands, it has a great variety which can be enjoyed along with a series of tourism activities that the Quislag Grande community can offer such as camping, horseback riding, photography, photography, hiking, etc., as well as a series of activities that the Quislag Grande community can offer, horseback riding, photography, hiking, kayaking, bird watching, fauna and flora, and climbing to the viewpoint. Finally, we propose a model tourism plan for the Quislag Grande community that is sustainable with an initial project to adapt the space of the Pishellik Cocha lagoon to attract tourists and provide ongoing training to the villagers, based on advertising marketing with the creation of a slogan "Your Natural Destination" and a logo.